Consummatory suppression due to incentive downshift is not a consequence of enhanced search behavior - Lopez Seal, María Florencia (2013)
Rats shifted from 32% to 4% sucrose solution consume less from the 4% solution than rats that experience only the 4% solution. This consummatory suppression, a phenomenon known as consummatory successive negative contrast (cSNC), is accompanied by an increase in other behaviors such as rearing, nose-downlocomotion,ambulation, sampling new sources and grooming.Despite a large body of studies on the cSNC, it remains to be determined whether reduced consumption is part of the direct response to the reward downshift or a by product of the increase in alternative competing behaviors. The objective of the present study was to determine if consummatory suppression would occur when most competing behaviors are prevented from occurring. Rats were trained either with 32% or 4% sucrose solution for ten days in restrainers that limited almost all movement. On the next ﬁve days, all subjects received the 4% sucrose solution and a robust suppression in drinking in the downshifted animals was observed. These results suggest that consummatory suppression is a direct consequence of incentive downshift and not a byproduct of the increase in competing behaviors.